Women's Rugby League: Positional Groups and Peak Locomotor Demands - Cummins, Cloe; Charlton, Glen; Paul, David; Shorter, Kath; Buxton, Simon; Caia, Johnpaul; Murphy, Aron (Frontiers in Sports and Active Living, 2021)
The aims of this study were to: a) use a data-based approach to identify positional groups within National Rugby League Women’s (NRLW) match-play and; b) quantify the peak locomotor demands of NRLW match-play by positional groups. Microtechnology (Global Navigational Satellite System [GNSS] and integrated inertial sensors; n = 154 files; n = 76 players) and match statistics (n = 238 files; n = 80 players) were collected from all NRLW teams across the 2019 season. Data-based clustering of match statistics was utilised to identify positional clusters through classifying individual playing positions into distinct positional groups. Moving-averages (0.5, 1, 2, 3, 5 and 10 minutes) of peak running and average acceleration/deceleration demands were calculated via microtechnology data for each player per match. All analysis was undertaken in R (R Foundation for Statistical Computing) with positional differences determined via a linear mixed model and effect sizes (ES). Data-based clustering suggested that, when informed by match statistics, individual playing positions can be clustered into one of three positional groups. Based on the clustering of the individual positions, these groups could be broadly defined as backs (fullback, wing and centre), adjustables (halfback, five-eighth and hooker) and forwards (prop, second-row and lock). Backs and adjustables demonstrated greater running (backs: ES 0.51-1.00; p < 0.05; adjustables: ES 0.51-0.74, p < 0.05) and average acceleration/deceleration (backs: ES 0.48-0.87; p < 0.05; adjustables: ES 0.60-0.85, p < 0.05) demands than forwards across all durations. Smaller differences (small to trivial) were noted between backs and adjustables across peak running and average acceleration/deceleration demands. Such findings suggest an emerging need to delineate training programs in situations where individual playing positions train in positional group based settings. Collectively, this work informs the positional groupings that could be applied when examining NRLW data and supports the development of a framework for specifically training female rugby league players for the demands of the NRLW competition.